Anorexia Nervosa, Anxiety, and the Clinical Implications of Rapid Refeeding - Kezelman, Sarah; Crosby, Ross D.; Rhodes, Paul; Hunt, Caroline; Anderson, Gail; Clarke, Simon; Touyz, Stephen (Frontiers in Psychology, 2018)
The current study aimed to examine the temporal relationship between anxiety symptoms and weight gain for adolescents with anorexia nervosa over the course of an inpatient admission targeting weight restoration through rapid-refeeding. Participants were 31 females presenting to a specialist inpatient unit. Psychometric assessments using standardized procedures were conducted to assess co-morbid anxiety diagnoses, and eating disorder symptom severity at admission and discharge. Study protocols were completed on a weekly basis over the course of their admission, and were compared with weekly BMI change. Multiple mixed-effects linear models with random intercepts were used to assess change in weight status and psychological variables. Results indicated a reduction in anxiety over the course of hospitalisation, however, there was no evidence to support a relationship between anxiety change and weight restoration. The clinical implications of these results are discussed and directions for future research recommended.